Combined Transcriptomics and Metabolomics Analyses in Grass Carp Under Anesthetic Stress - Wang, Tianwei; Wang, Yali; Liu, Xueting; Gao, Xiaoning; Hu, Kun (Frontiers in Cellular and Infection Microbiology, 2022)
Ctenopharyngodon Idella, as a common freshwater bony fish, is more susceptible to various diseases than other carp species, so it has been proposed as a test organism for toxicological analysis In this study, C. idella were anesthetized with MS-222 and 2-PE, and the related anesthetic mechanism and toxic effects were revealed by transcriptomics and metabolomics analyses. When the concentration of MS-222 was 80 mg/L and 200 mg/L, 179 and 887 differentially expressed genes (DEGs), respectively, were identified in the brain tissue of C. idella. When the concentration of 2-PE was 0.6 mL/L and 1.2 mL/L, 498 and 514 DEGs were identified. The DEGs associated with MS-222 treatment were enriched in immune pathways, lipid metabolism, amino acid metabolism, and various signaling pathways; DEGs associated with 2-PE treatment were enriched in immunity and amino acid metabolism. In total, 304 metabolites were identified using a combination of positive and negative ion modes in mass spectrometry. The common differential metabolites identified in the MS-222 high and low concentration groups were 20-HETE and 12(R)-HETE; the common significant differential metabolite identified in the 2-PE high and low concentration groups was salidroside. In combination with the transcriptomics analysis and metabolomics analysis, the results showed that with the MS-222 and 2-PE concentrations used in this experiment, the metabolism of arachidonic acid in C. idella was inhibited by MS-222, and 2-PE affected the upstream and downstream metabolic pathways of arachidonic acid metabolism, thereby affecting the metabolism of arachidonic acid. Both anesthetics induce sedation by affecting related metabolites that affect stress response and autoimmunity. Metabolomics results showed that neither anesthetic had a significant effect on cortisol expression.